Coat of many pockets : managing classroom interactions - Mackay, Jenny ([NetLibrary]., 2006)
Coat of Many Pockets: Managing classroom interactions isintended for beginning and returning teachers as well as foreducators wanting to enhance their behaviour managementskills. It is a handbook for understanding the aims anddeveloping the practical techniques involved in managingindividuals and groups in the classroom, based on a synthesisof major behaviour management thinkers. The book shows teachers how to replace their customaryreactions to diffi cult behaviour with skilled responses thatcontain the behaviour while engaging the student. The readerwill learn practical social, emotional and.